Beyond spirituality and mysticism in the Patristic era - Ludobikos, Nikolaos (Analogical identities., 2019)
A book about the possibility of retrieving a concept of selfhood from Patristic theology, beyond the dichotomies of mind and body, or person and nature. Is it possible for nihilism and an ontology of personhood as will-to-power to be incubated in the womb of Christian Mysticism? Is it possible that the modern ontology of power, which constitutes the core of western metaphysics, has a theological grounding? Has Nietszche reversed Plato or, more likely, Augustine and Origen, re-fashioning in a secular framework the very essence of their ontology? Is there a non-ecstatic understanding of Christian selfhood? Patristic theology seems to provide us with an alternative understanding of selfhood, beyond what has been referred to as 'Christian Platonism'. This book strives to decipher, retrieve, and re-embody the underlying mature Patristic concept of selfhood, beyond the dichotomies of mind and body, or person and nature